2017
DOI: 10.1039/c6nr06795f
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed weak antilocalization in the topological insulator Bi2Se3proximity coupled to antiferromagnetic NiO

Abstract: Time-reversal symmetry (TRS) breaking of the topological insulators (TIs) is a prerequisite to observe the quantum anomalous Hall effect (QAHE) and topological magnetoelectric effect (TME). Although antiferromagnetism as well as ferromagnetism could break the TRS and generate massive Dirac surface states in the TIs, no attention has been paid to the antiferromagnet-TI heterostructures. Herein, we report the magnetotransport measurements of BiSe proximately coupled to antiferromagnetic NiO. Thin films of BiSe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Magnetotransport in such a heterostructure (NiO–Bi 2 Se 3 ) showed suppressed WAL, and even WL at a low magnetic field in a sample with ultrathin (5 nm) TI. [ 115 ] Whereas these results are encouraging, in order to unambiguously detect the proximity effect, further experimental investigations are necessary.…”
Section: Recent Results In Topological Insulator (Ti) – Magnetic Materials (Mm) Heterostructuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Magnetotransport in such a heterostructure (NiO–Bi 2 Se 3 ) showed suppressed WAL, and even WL at a low magnetic field in a sample with ultrathin (5 nm) TI. [ 115 ] Whereas these results are encouraging, in order to unambiguously detect the proximity effect, further experimental investigations are necessary.…”
Section: Recent Results In Topological Insulator (Ti) – Magnetic Materials (Mm) Heterostructuresmentioning
confidence: 98%
“…When a clean interface is obtained between a TI and a MM, the magnetic moments in the MM can align spins in parallel [ 104 ] or antiparallel [ 109 ] manner in the TI through direct exchange interaction. [ 109–116 ] This interaction requires direct wavefunction overlap and hence is inherently short ranged; thus for the TI surface state which decays exponentially into the TI bulk, the magnetization decays rapidly as well. [ 105 ] Similarly, only the magnetic moments of the layer next to the MM have any relevant impact.…”
Section: Mechanisms Of Proximity Effectmentioning
confidence: 99%
“…Kandala et al performed electrical transport measurement of GdN/Bi2Se3, finding that a GdN overlayer results in suppression of weak anti-localization at the top surface of Bi2Se3 [492]. Similar observation of the suppressed weak antilocalization in Bi2Se3 proximity coupled to antiferromagnetic NiO was reported by Bhowmick et al[493]. By demonstrating the MR effect, Yang et al[494] and Wei et al[492] observed proximity-induced ferromagnetism at the interface of EuS/Bi2Se3 prepared via both PLD and MBE deposition techniques respectively, although the effect observed is limited to low temperature (< 22 K) due to the low Tc of EuS.…”
mentioning
confidence: 56%
“…Surprisingly, tight-binding calculations by Oroszlány and Cortijo showed that even anantiferromagnetic interface with staggered magnetization can lead to proximityinduced gap opening in TI surface states [183], making AFMI-TI heterostructures even more promising. Mag-netotransport in such a heterostructure (NiO-Bi 2 Se 3 ) showed suppressed WAL, and even WL at a low magnetic field in a sample with ultrathin (5 nm) TI [108]. Whereas these results are encouraging, in order to unambiguously detect the proximity effect, further experimental investigations are necessary.…”
Section: Antiferromagnetic Proximity Effectmentioning
confidence: 92%
“…When a clean interface is obtained between a TI and a MM, the magnetic moments in the MM can align spins in parallel or antiparallel manner in the TI through direct exchange interaction [102][103][104][105][106][107][108][109]. This interaction requires direct wavefunction overlap and hence is inherently short ranged; thus for the TI surface state which decays exponentially into the TI bulk, the magnetization decays rapidly as well [98].…”
Section: Direct Exchange Couplingmentioning
confidence: 99%